Efficacy of an implementation package on documentation of central venous catheter insertions: an observational study. Issue 2 (28th April 2021) - Linné, Erik; Adrian, Maria; Bentzer, Peter; Kander, Thomas
Abstract : Background: Proper documentation of central venous catheter (CVC) insertions in electronic healthcare records is the basis for good follow-up and quality assurance. We have noted serious deficiencies in the documentation of CVC insertions and introduced an implementation package with the purpose of increasing the completeness of this documentation. The aim of the present study was to estimate the effect of the implementation package by assessing the proportion of missing data before and after the introduction of the implementation package. Methods: In this single centre observational study, data from CVC insertion templates in a common electronic health record were extracted and analysed after introducing the implementation package. The package included adoption of new local CVC-directions, a new updated CVC-insertion template in the regional common electronic health record and a review of all CVC-insertion templates with a reminder to the inserting physician to supplement missing data. The proportion of terms with missing data was reviewed and also compared with the proportion of missing data in a study prior to the introduction of the package. Results: In total, 7126 CVC-insertion templates were included. Of these 5539 (78%) were without missing data for any of the 13 predefined variables. Completed insertion templates for three common terms increased from 38% prior to the introduction of the implementation package to 93%, which represents an absolute reduction for missing data of 55% (95% CI 53% to 56%, p<0.0001). Conclusion: The implementation package was highly effective in increasing the proportion of fully documented CVC insertions.